The Effect of Work Motivation Factors on Job Satisfaction in XY company - Suhartono Suhartono (iBuss Management, 2015)
The reason behind this research is because XY company faces low productivity and low employee motivation problems. The purpose of this research is to give solutions towards XY’s problem. Respondent of this research is employee of production division of XY Makassar. Sampling method that has been used for this research is stratified sampling method on all division inside production division in XY Makassar. The method being used is multiple linear regression analysis and this research also use work motivations factor as the independent variables and job satisfaction as the dependent variable. Results of the research has shown that simultaneously work motivations factor have significant influence on job satisfaction while individually, only salary and job security are the factors that have significant influence on job satisfaction. Researcher has made several suggestions to XY in order for them to improve job satisfaction. Keywords: Work Motivation, Job satisfaction, Herzberg Theory, Hygiene Theory